Pelatihan dan Pendampingan Pembuatan Pupuk Organik dari Limbah Organik di Desa Ambalkliwonan Kabupaten Kebumen - Moh. Bahrun; Rasyid Zuhdi; Dwiyono Waluyo; Dyah Widi Astin Intansari; Afrie Nardiansyah; Isnaini Lilis Elviyanti; Titi Maemunah; M Izzudin; Hamdani Hamdani; Hindami Hindami; Priyatno Priyatno; Noor Adi Wibowo; Teguh Arief Rahmanto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Waste is one of the unsolved problems. Waste originating from livestock is one of the problems faced by the residents of Ambalkliwonan Village, Kebumen Regency. This waste belongs to the type of organic waste that is left alone by cattle farmers and causes an unpleasant odor, still it can also drive the growth of disease-causing microorganisms in the surrounding environment. Waste from cow dung can be utilized by turning it into fertilizer. The service location is in Ambalkliwonan Village, Ambal District, Kebumen Regency, Central Java. Some people who work as farmers and cattle breeders are targeted in community service programs. The objectives to be achieved from training activities and mentoring in the use of organic cow dung into organic fertilizer are to provide information and knowledge and raise awareness in the community about the use of cow dung so as not to cause environmental pollution and raise public awareness of the importance of using organic fertilizers so that it will minimize expenditure on the purchase of chemical fertilizers for rice plants. The method applied to this community service activity is by presenting material which is then carried out by direct practice to make organic and solid fertilizer. Then an evaluation of the products produced and all the processes carried out by the community. The results of community service activities show that community members of the training and mentoring program can make their own organic and solid fertilizer. This community service has succeeded in increasing public awareness of the importance of healthy and creative living, and the use of organic fertilizers in farming. Keywords: Organic waste, organic fertilizer, organic agriculture